Visible wavelength FBG sensors - Ching, Wei Wen (2014)
The project is to carry out an investigation and development of a modular FBG sensor system that can be mass-produced at an economical cost. By operating FBG sensors in/near the visible light spectrum, it allows the modular FBG sensor to utilize small and cheap super luminescent diode or light-emitting diode and charge-coupled detector as the light source and detector. This would significantly reduce the size and manufacturing cost of the entire modular FBG sensor.